The Procedure for Measuring Fuel Pressure on an Injection Motorbike Uses a Pressure Gauge: Prosedur Pengukuran Tekanan Bahan Bakar Pada Sepeda Motor InjProsedur pengukuran tekanan bahan bakar pada sepeda motor injeksi menggunakan pressure gaugeeksi Menggunakan Pressure Gauge - Robikh Arafat, Diyas; Firdaus, Rachmad (Universitas Muhammadiyah Sidoarjo, 2024)
This study aimed to design and test a fuel pump pressure tester for injection motors to measure fuel pressure and determine whether the fuel pump is working properly. The qualitative method was used in the design process, which included creating design concepts, observation, and data processing. A literature review was conducted to strengthen the research results. The functional test in the final process showed that the tool could work well and provide information in measuring fuel pressure from the fuel pump. The implication of this study is that the fuel pump pressure tester can be used to prevent engine failure and improve engine performance. Highlight: Qualitative method used in the design process Literature review conducted to strengthen research results Functional test showed tool can measure fuel pressure accurately Keywords: fuel pump pressure tester, injection motors, fuel pressure, engine failure, engine performance.